Complex Origins and History of the Relict Fennoscandian Ringed Seals - Tange Olsen, Morten; Löytynoja, Ari; Valtonen, Mia; Knudsen, Steen W.; Bang, Sofie; Gunnersen, Casper; Rosing‐Asvid, Aqqalu; Ferguson, Steven H.; Dietz, Rune; Kovacs, Kit M.; Lydersen, Christian; Jernvall, Jukka; et al. (Wiley-Blackwell, 2025)
Spatiotemporal environmental heterogeneity is a major evolutionary driver, which can cause profound phylogeographic complexity, particularly at the periphery of species ranges. Ringed seals display a highly disjoint distribution, occurring in high abundance throughout the circumpolar Arctic, as well as in the Baltic Sea, Lake Saimaa and Lake Ladoga. These relict Fennoscandian ringed seals were traditionally regarded as originating from a single colonisation event after the Last Glacial Maximum (LGM), but recent studies have challenged this perception. Here, we analyse 246 mitogenomes and 180 skulls to unravel the diversity and spatiotemporal pattern of diversification in Fennoscandian ringed seals. Contrary to previous assumptions, our results reveal a complex evolutionary history characterised by pre-LGM diversification from Arctic ringed seals and possibly several Fennoscandian colonisation events. We hypothesise that Saimaa seals originate from Arctic ringed seals, from which they diverged prior to their arrival in Lake Saimaa. Ladoga seals appear to also originate from the Arctic, with secondary colonisation events from paleo-Skagerrak–Kattegat–Baltic, while the Baltic ringed seals have mixed evolutionary origins. Lake Saimaa and, to some extent, Lake Ladoga ringed seals have experienced a loss of diversity and evolved divergent skull morphologies, likely as a result of colonisation bottlenecks, isolation and dietary specialisation, while Baltic Sea ringed seals have retained remarkably high levels of genetic and morphological diversity. Our study supports the classification of Saimaa, Ladoga and Baltic ringed seals as distinct taxa and highlights the need for management and conservation efforts to mitigate cumulative impacts of human activities and climate change on Fennoscandian ringed seals.
Keywords: climate change; mitogenome; morphometrics; phylogeography; quarternary